Ta’tsir Thariqah Al-Sual wa Al-Jawab li Tarqiyah Fahmu Thulab li Mufradat Al-Arabiyah - Khairul Adam; Mulyani Maiza (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
The researchers found problems in grade 5 at SD Jam'iiyatul Hujjaj Bukittinggi , The difficulty of students in teaching the Arabic language in understanding vocabulary is very low, This makes it difficult for students to understand each material presented. The objectives of this research are to know the effect of the question and answer method to improve students’ vocabulary understanding, to improve students’ vocabulary understanding so that students can easily understand the meaning of each vocabulary. This study used quantitative research with a group pretest-posttest design. Researchers took samples in this research experimental class of 28 students and control class of 28 students.The tools used for collecting data were observation, examination, and documentation. and student learning outcomes using the question-and-answer method through media images of 5th grade elementary school students. Based on the acquisition of an average value of 56, This is also proven through the calculation of "T." Calculate more than the "T" Table, namely 2,463.Then H0 is rejected and Ha is accepted. So it can be concluded about the effectiveness of the use of the question and answer method through picture media for students in grade 5 at SD Jam'iiyatul Hujjaj Bukittinggi.